2010
DOI: 10.1158/0008-5472.can-09-2153
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Melanoma Cells Capable of Propagating Tumors from a Single Cell

Abstract: Questions persist about the nature and number of cells with tumor-propagating capability in different types of cancer, including melanoma. In part, this is because identification and characterization of purified tumorigenic subsets of cancer cells has not been achieved to date. Here, we report tumor formation after injection of single purified melanoma cells derived from three novel mouse models. Tumor formation occurred after every injection of individual CD34+p75− melanoma cells, with intermediate rates usin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
92
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(108 citation statements)
references
References 33 publications
13
92
3
Order By: Relevance
“…Notably, in these conflicting reports and other studies, different enzymatic procedures have been used to prepare cell fractions from solid melanoma samples. Tumors have been mechanically dissociated followed by enzymatic digestion with collagenase (8), a mix of collagenase and dispase (9), or collagenase and trypsin (10,11,21). Therefore, we addressed whether these different tumor digestion protocols might affect detectability of surface markers used to directly isolate putative tumorigenic melanoma cell populations.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, in these conflicting reports and other studies, different enzymatic procedures have been used to prepare cell fractions from solid melanoma samples. Tumors have been mechanically dissociated followed by enzymatic digestion with collagenase (8), a mix of collagenase and dispase (9), or collagenase and trypsin (10,11,21). Therefore, we addressed whether these different tumor digestion protocols might affect detectability of surface markers used to directly isolate putative tumorigenic melanoma cell populations.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we described a GEM model in which expression of oncogenic BRAF V600E cooperates with PTEN silencing to pro-mote metastatic melanoma (9,26,27). Given the low frequency of PIK3CA mutations in human melanoma, we resolved to test the role of PI3K signaling in cooperation with mutationally activated BRAF V600E in melanomagenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The use of sensitive mouse models, such as the NOD/SCID IL2R_(null) mice, demonstrated that cell isolation through p75NTR does not enrich melanoma CSC, and melanoma cells are able to metastasize independently from their expression pattern, being able to reverse their phenotype through clonal expansion (Quintana et al, 2010;Civenni et al, 2011). Consistently, in another study CD34-neg/p75NTR-pos cells from mouse melanomas only rarely form tumors, while the p75NTR-negative counterpart frequently forms tumors, depending on CD34 expression (Held et al, 2010). This suggests that although some lines of evidence point at p75NTR as a good marker for the isolation of melanoma CSC, it may not be the right candidate.…”
Section: Fig 3 Nts and Their Receptors In Melanoma Biologymentioning
confidence: 77%
“…The "Cancer Stem Cell hypothesis" states that within tumor heterogeneity, only few cells are responsible for tumor initiation and maintenance, sharing with normal stem cells the ability to self renew and to persist in the tissue for years. Although in some tumors, such as leukemia, the CSC model is valid, in melanoma, cells able to initiate tumor formation are not a rare population (Quintana et al, 2010;Held et al, 2010;Roesch et al, 2010). Given the role of NTs and their receptors in melanoma biology, this complex network of growth factors is likely to be involved both in melanoma recurrence and metastasis in the patients.…”
Section: Fig 3 Nts and Their Receptors In Melanoma Biologymentioning
confidence: 99%